2018
DOI: 10.1021/acs.analchem.7b04666
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Label-Free Fluorescent Probe Based on G-triplex DNA and Thioflavin T

Abstract: G-triplexes have recently been identified as a new kind of DNA structures. They perhaps possess specific biological and chemical functions similar as identified G-quadruplex but can be formed by shorter G-rich sequences with only three G-tracts. However, until now, limited G-triplexes sequences have been reported, which might be due to the fact that their stability is one of the biggest concerns during their functional studies and application research. Herein, we found a G-rich sequence (5'-TGGGTAGGGCGGG-3') w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…The utility of ThT is rooted in its “turn‐on” response—a dramatic enhancement (up to thousand‐fold increase) in fluorescence intensity in the presence of amyloids. Complexes with certain macrocycles, oligonucleotides, and other non‐amyloid‐forming proteins also show substantial turn‐on responses. Fluorescence of ThT is also sensitive to other environmental factors including temperature, pressure, solvent viscosity, and pH .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of ThT is rooted in its “turn‐on” response—a dramatic enhancement (up to thousand‐fold increase) in fluorescence intensity in the presence of amyloids. Complexes with certain macrocycles, oligonucleotides, and other non‐amyloid‐forming proteins also show substantial turn‐on responses. Fluorescence of ThT is also sensitive to other environmental factors including temperature, pressure, solvent viscosity, and pH .…”
Section: Methodsmentioning
confidence: 99%
“…We also used SILIF to examine complexation of ThT + with other binding partnersi nt he gas phase. We tested two molecules known to inducet urn-on responses in solution (Figure S5, SI): as econd macrocycle-cucurbit [7]uril (CB7), [3] and a biomolecule-the 22AG human telomeric G-quadruplex DNA. [6] [ThT+ +CB7] + ,[ ThT+ +CB7] 2 + and [ThT+ +22AG] 5À ,w hich were the most abundantc omplexes detected under our mass spectrometry conditions, were each individually stored and irradiated at multiple wavelengths.H owever,f luorescencee mission was not detected from any of these complexes ( Figure S6, SI).…”
mentioning
confidence: 99%
“…Circular dichroism (CD) measurements were performed on a Chirascan CD spectrometer (Applied Photophysics Ltd., UK) using a 1 mm path length quartz cuvette at room temperature under the following parameters: range 200-500 nm, scanning speed 200 nm min À1 , bandwidth 1 nm, response time 0.5 s. 37 The 12% native polyacrylamide gel electrophoresis (nPAGE) was operated at the Bio-Rad electrophoresis analyzer (Bio-Rad, USA) using 80 V constant voltage at room temperature for 1 hour in 1Â TBE buffer (90 mM Tris-boric acid, 2 mM EDTA, pH 8.0). Then, the gel was stained with GoldView I for another 30 minutes with continuous rotation and nally photographed with a Bio-Rad ChemDoc XRS (Bio-Rad, USA).…”
Section: Apparatus and Instrumentsmentioning
confidence: 99%
“…36 Fortunately, Zhou et al reported a new G-rich sequence-based DNA nanostructure, G-triplex, which has similar functions to G-quadruplex but only consists of 13 bases. 37 Herein, we propose a label-free, ultra-low background signal and ultra-high signal-to-noise ratio DNA nanomachine, which is based on the palindromic fragment-incorporated multifunctional hairpin probe (P-HP)-assisted symmetric exponential amplication reaction (S-EXPAR), with G-triplex/ThT complex as the signal reporter. In this experiment, the p53 gene was selected as the model analyte because it is mutated in more than 50% of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence method is widely used in the biosensing field because of its simplicity and high‐throughput capability ,. Fluorescence method has been explored to detect DNA polymerase activity .…”
Section: Introductionmentioning
confidence: 99%